The Use of Environmental Sensors on Optimizing Natural Resource Management with Technology Integration in Environmental Accounting Information Systems - Renaldo, Nicholas; Susanti, Wilda; Chandra, Teddy; Jahrizal, Jahrizal; Junaedi, Achmad Tavip; Azim, Fauzan; Tendra, Gusrio; Ramdani, Ramdani; Veronica, Kristy; Ramadhani, Ramadhani (Interconnection: An Economic Perspective Horizon, 2024)
The use of environmental sensors in EAIS goes beyond traditional accounting by embedding environmental sustainability into the core of financial management. It enables companies to meet sustainability targets more effectively by offering visibility into their environmental footprint, leading to better strategic planning, risk management, and compliance with environmental regulations. The study follows a descriptive and exploratory research design to identify the current challenges and opportunities in integrating environmental sensors into EAIS. The integration of environmental sensors into Environmental Accounting Information Systems (EAIS) represents a significant innovation in the field of environmental accounting. By enabling real-time data collection and continuous monitoring of environmental impacts, this system allows businesses to manage resources more effectively, ensure regulatory compliance, and enhance corporate transparency. The sensor-integrated EAIS not only optimizes resource use but also helps businesses align their operations with sustainability goals, providing a comprehensive view of both environmental and financial performance.